Insect abundance and pest prevalence across landscape types and seasons in arabica coffee plantations of West Java, Indonesia (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Maharani Y, Utari A, Andriani TS, Maxiselly Y, Rasiska S, Sudarjat, Hutapea D, Hidayat P. 2025. Insect abundance and pest prevalence across landscape types and seasons in arabica coffee plantations of West Java, Indonesia. Biodiversitas 26: 5438-5448. West Java is renowned for being a leading producer of high-quality arabica coffee in Indonesia and has received international recognition for its products. The presence of insects, particularly pests, and the extent of the damage they cause are critical factors that influence coffee productivity. This study investigated the effects of landscape composition and climate on insect abundance and pest damage severity in Arabica coffee plantations in West Java, Indonesia. Sampling was conducted across three landscape types: settlements, agricultural, and agroforestry systems, during dry and rainy seasons in Cilengkrang and Pangalengan Districts. For each landscape type, five plots measuring 10 × 10 m were established for data collection. Insect sampling combined brocap traps, beating sheets, a yellow pan trap, and direct collection, while pest intensity was evaluated on fruiting coffee plants. The study revealed that insect community composition varied significantly across coffee plantations, influenced by landscape type and seasonal changes. Insect abundance was notably higher during the dry season, with 5,938 individuals counted, compared to 2,024 individuals during the rainy season. Climatic conditions had a significant impact on insect distribution and community structure. Non-Metric Multidimensional Scaling (NMDS) revealed more distinct community composition among landscapes in the dry season, while rainy-season communities were more homogeneous. Herbivorous insects were most abundant in agricultural areas, regardless of the season. Pest damage was mostly low, except for Hypothenemus hampei (coffee berry borer), which caused consistently high damage in settlements and agricultural areas regardless of season and exceeded economic thresholds (>5%). Findings highlight the strong influence of landscape structure and seasonal climate on insect community dynamics and pest pressure. The study's implications for pest management practices suggest that promoting habitat heterogeneity through agroforestry and diversified vegetation could enhance natural pest control and support sustainable Arabica coffee production.
Keywords: Agricultural, agroforestry systems, dry season, herbivorous insects, rainy season